A new species of Parapanteles Ashmead (Hymenoptera: Braconidae) from India reared from Abisara echeria Stoll (Lepidoptera: Riodinidae) with key to the Indian Parapanteles species - Gupta, Ankita; Pereira, Blaise; Churi, Paresh V. (Zootaxa, 2013)
A new species of gregarious endoparasitoid, Parapanteles echeriae Gupta, Pereira & Churi, sp. nov., bred from Abisara echeria Stoll (Lepidoptera: Riodinidae) on host plant Embelia sp. (Myrsinaceae), is described and illustrated from Mumbai, Maharashtra, India. Abisara echeria, commonly known as plum judy, is a small striking butterfly prevalent in Asia. This is the first ever record of a parasitic wasp associated with Abisara. Parapanteles echeriae is distinguished from P. sireeshaae Ahmad & Akhtar in having propodeum with areola 1.2´ as long as wide; anterior diagonal carina meeting anterior margin of propodeum in one half; veins r and 2RS of fore wing merging in a smooth curve; yellow coloured legs and tegulae brownish black. A key to the Indian species of Parapanteles is also provided.